Establishing a Eukaryotic Pichia pastoris Cell-Free Protein Synthesis System - Zhang, Lingkai; Liu, Wan-Qiu; Li, Jian (Frontiers in Bioengineering and Biotechnology, 2020)
In recent years, cell-free protein synthesis (CFPS) systems have been used to synthesize proteins, prototype genetic elements, manufacture chemicals, and diagnose diseases. These exciting, novel applications lead to a new wave of interest in the development of new CFPS systems that are derived from prokaryotic and eukaryotic organisms. The eukaryotic Pichia pastoris is emerging as a robust chassis host for recombinant protein production. To expand the current CFPS repertoire, we report here the development and optimization of a eukaryotic CFPS system, which is derived from a protease-deficient strain P. pastoris SMD1163. By developing a simple crude extract preparation protocol and optimizing CFPS reaction conditions, we were able to achieve superfolder green fluorescent protein (sfGFP) yields of 50.16 ± 7.49 μg/mL in 5 h batch reactions. Our newly developed P. pastoris CFPS system fits to the range of the productivity achieved by other eukaryotic CFPS platforms, normally ranging from several to tens of micrograms protein per milliliter in batch mode reactions. Looking forward, we believe that our P. pastoris CFPS system will not only expand the CFPS toolbox for synthetic biology applications, but also provide a novel platform for cost-effective, high-yielding production of complex proteins that need post-translational modification and functionalization.